The impact of environmental information disclosure on the cost of debt: evidence from China - Yongliang Yang; Jing Wen; Yi Li (Journal of Applied Economics, 2024)
With the growing attention being paid to environmental issues by the public, environmental information disclosure (EID) has become a vital means for firms to convey their social responsibility and an important information source for lending institutions to assess firm credit risk. Based on the data of listed companies in China, a two-way fixed effects model is applied in this study to determine the impact of EID on the cost of debt. It reveals that EID can decrease companies’ cost of debt and that both CEO duality and ownership concentration play vital roles in this relationship. After the consideration of endogeneity problems and robustness testing, the conclusions remain valid.